Waste heat driven cooling at beef processing facilities - Colosimo, Samuel Paul, author; Bandhauer, Todd M., advisor; Jathar, Shantanu, committee member; Dillon, Jasmine, committee member (Colorado State University. Libraries, 2021)
Waste heat recovery technologies present an opportunity to utilize typically wasted energy to reduce overall energy consumption by producing mechanical work, electricity, heating, or cooling. In this study, the technoeconomic performance of a turbo-compression cooling system (TCCS) driven by waste heat from boiler exhaust gas produced at beef processing facilities is investigated. The cooling produced by the TCCS is integrated to the primary refrigeration system (PRS) of a beef processing facility to provide condenser subcooling, which enhances the performance of the PRS and produces refrigeration energy savings. Further savings are produced by rejecting condenser heat from the TCCS to feedwater entering the boiler, allowing for a reduction in boiler natural gas consumption. Process level natural gas and water data was collected at a beef processing plant and used to calculate waste heat availability and boiler water flow rate. TMY3 weather data for five cities was used to model a beef plant refrigeration system with a condenser cooling tower. To justify the installation of a TCCS, the performance and economics of the system are compared to three technologies: an electrically driven dedicated mechanical subcooler (DMS), an organic Rankine cycle (ORC), and a feedwater economizer (FWE). The results of this study show that a TCCS used to subcool the PRS yielded the highest annual savings of the four technologies. A coupled thermodynamic, heat transfer, and economic model was produced to determine the capital cost, payback period, and net present value of each technology. Then, an optimization study was carried out for the TCCS, DMS, and ORC to minimize payback period and maximize net present value by varying the effectiveness values of the heat exchangers. The feedwater economizer was found to have the lowest average payback period of 0.92 years at an initial investment cost of $50,815. The average net present value of the FEW across the five cities was found to be $245,000. The ORC had the second lowest payback period of 1.82 years at an initial investment cost of $95,000. To achieve such a low payback period, the ORC produces almost no electricity, generating revenue solely through boiler feedwater heating. The net present value of the ORC was the second lowest at $175,000. The TCCS was found to have the third lowest average payback period of 2.22 years at a capital cost of $328,000, and the highest net present value of $429,000. The DMS was found to have the slowest payback period of 3.88 years at an investment cost of $465,000, and the lowest net present value of $84,000.
Keywords: food processing; techno-economics; waste heat recovery; heat transfer; energy efficiency; thermal energy